Revitalisasi Sastra Lisan sebagai Materi Pengayaan Literasi di Lingkungan PKBM Tentrem Berdaya - Zainah Asmaniah; Winka Naida; Lina Siti Nurwahidah; Umi Kulsum; Puput Putri (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity was motivated by the low level of integration of local wisdom into the formal literacy curriculum at PKBM Tentrem Berdaya, which has led to the marginalization of regional oral literature. The primary objective of this program is to improve students' reading comprehension skills through the exploration and adaptation of oral literary values. The method employed is Participatory Action Research (PAR), implemented through intensive training, mentoring, and writing workshops. The results of the program demonstrate measurable improvements in students' cultural literacy and language skills. This revitalization effort has successfully bridged the gap in cultural literacy while providing contextual learning resources for students. This initiative is expected to serve as a strategic reference for non-formal educational institutions in integrating local wisdom to strengthen the foundation of community cultural literacy.